Biochemistry / Jeremy M Berg - Berg, Jeremy M.Author
With new co-authors Jeremy Berg and John Tymoczko, Biochemistry" 5th edition has expanded integration of evolution, more chemical and structural insights, and a web based media component created simultaneously with the text.